PENDIDIKAN ISLAM DI INDONESIA PADA ZAMAN PENJAJAHAN BELANDA DAN JEPANG - Subandi Subandi; Bahaking Rama; Andi Achruh (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
Islamic education during the Dutch and Japanese occupation, that Islamic education during the Dutch colonial period in Indonesia, the Dutch colonial government severely limited the activities of madrasas and teachers who taught at madrasas. They do that because they are afraid of the Muslim Ummah which has started to develop. Meanwhile, when Japan was in power, Islamic education was slightly freer than during the Dutch colonial era. However, Japan, with its mission, required teachers to learn Japanese in giving lessons and changing Dutch to Indonesian, including requiring respect for the Tenno (Emperor). This is what the Islamic leaders did not accept, so they were eventually arrested.